DEVELOPING A FREIGHT FORWARDING MARKETING STRATEGY TO ATTRACT NEW CUSTOMERS FOR PT SAFE LOGISTICS INTERNATIONAL - Rizka Amalia; Harimukti Wandebori (RADJA PUBLIKA, 2026)
This study investigates the root causes of PT SLI’s slow customer acquisition and formulates a practical marketing strategy aligned with the firm’s operational capacity and the evolving external environment. The research rests on three key assumptions: market shifts and customer expectations shape acquisition challenges, the company possesses internal capabilities suitable for a differentiation strategy, and structured marketing combined with digital enhancements can strengthen competitiveness. Based on these premises, the study aims to analyze the dynamics of the B2B freight forwarding market, evaluate internal and external factors affecting PT SLI’s marketing performance, and propose an applicable plan to expand its customer base. A qualitative case study method was applied, using open-ended questionnaires distributed to representatives of three manufacturing firms to obtain insights into customer expectations, forwarder selection considerations, and common service issues. Additional information was collected through informal interviews with PT SLI’s Director, supplemented by secondary data from academic literature, industry reports, logistics indices, and company documents to support triangulation. The analysis employed multiple frameworks, including STP, PESTEL, Porter’s Five Forces, competitor analysis, RBV, Value Chain, SWOT, and TOWS. Findings indicate several opportunities in Indonesia’s growing manufacturing sector, government efforts to streamline trade processes, and rising logistics demand. However, PT SLI faces strong competitive pressure, high supplier bargaining power in global shipping lines, and increasing digital demands. Internally, the company benefits from strong relationships with shipping lines, reliable documentation abilities, consistent operations, and customer loyalty. Its main weaknesses lie in the absence of formal marketing, limited digital presence, fragmented workflows, and reliance on senior employees’ tacit knowledge. TOWS analysis suggests differentiation as the most suitable strategy, supported by operational standardization, digital upgrades, marketing renewal, and improved knowledge management. The study contributes to understanding strategic development in traditional logistics firms and offers PT SLI a feasible roadmap for sustainable growth.